STATUS AGAMA ANAK BAGI IBUBAPA YANG MEMELUK AGAMA ISLAM DI MALAYSIA - Nasohah, Zaini; Moursi Elseoudi, Abdel Wadoud Moustafa; Mohd Kashim***, Mohd Izhar Ariff (Jurnal Syariah, 2010)
Cases on conversion to Islam always raises conflict. This phenomenon occured due to the existance of two different jurisdiction, they are Shariah Court and Civil Court. Among the conflicts that usually raise attention are on the status of dissolution of marriage, rights of custodianship, maintenance of children, inheritance and the religious status of children. However, discussion on children’s religion usually would include on custodianship and guardianship rights. This article aims to discuss jurists view on the isuue of children’s religion. The discussion will also refer to decision made by Civil Court on the matter concern. Analysis made on the decided case has shown that there are several interpretation that has been made on the provision of Article 12(4) of the Federal Constitution on deciding the children religious’ status, as decided by Federal Court in Shubashini’s case. Referring on the decision made by Federal Court, it would be appropriate to adhere to interpretation given on Article 12(4), to ensure the provision been respected and accepted as reference to society of multi-religious background in Malaysia. In other aspect, everyone should observe to the special position enjoys by Islam as the religion of the Federation.